Comparison of the Effectiveness of Gestalt-Based Play Therapy and Parent-Centered Play Therapy on Academic Self-Efficacy among Female Students in the Second Cycle of Elementary School - Darvish, Mahdieh; Rezakhani, Simindokht; Dokaneifard, Farideh (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to compare the effectiveness of Gestalt-based play therapy and parent-centered play therapy on academic self-efficacy among female students in the second cycle of elementary school. The research method was quasi-experimental, using a pretest–posttest design with a control group and a two-month follow-up. The statistical population included female students in the second cycle of elementary school, aged 9 to 11 years, who were studying in public elementary schools in District 8 of Tehran during the 2024–2025 academic year. A total of 45 students were selected for two experimental groups and one control group, with 15 participants in each group, using convenience sampling, and responded to the Academic Self-Efficacy Questionnaire developed by Morgan and Jinks (1998). The results of repeated-measures analysis of variance and the Bonferroni post hoc test showed that Gestalt-based play therapy and parent-centered play therapy effectively improved academic self-efficacy among female students in the second cycle of elementary school (p ≤ .001). Gestalt-based play therapy showed a greater effect on increasing academic self-efficacy. Based on the findings, both approaches play valuable roles in supporting children’s psychological and academic development and have distinct strengths that can provide interventions tailored to specific therapeutic goals.